Effect of copper on interfacial reaction and microstructure of soldering on aluminum substrate - Jiahui Li; Yu-An Shen; Hiroaki Tatsumi; Hiren Kotadia; Runhua Gao; Hiroshi Nishikawa (Journal of Materials Research and Technology)
Interfacial reactions and microstructure evolution of Al/Sn-3.5mass%Ag (SA)/Al, Al/Sn-3.0mass%Ag-0.5mass%Cu (SAC305)/Al, and Cu/SA/Al joints were investigated in this study. The microstructure of the intermetallic compound (IMC) was studied at soldering temperature of 250 °C and a thermal aging temperature of 150 °C for 100, 300, and 1000 h. The Ag3Sn precipitated in the Al/SA/Al solder matrix coarsened with increasing aging time, while the morphology of the Ag2Al formed and attached to the Al substrate remained stable. The volume and distribution of Al2Cu were significantly affected by the Cu concentration introduced via the solder or the Cu substrate. The Al2Cu distributed as a layer next to the Ag2Al layer in Al/SAC/Al joints, which was distributed homogeneously in the solder matrix for the single side soldering performed in the previous study. Massive Al2Cu was observed in Cu/SA/Al as soldered and would continuously form with further Cu and Al diffusion caused by thermal aging. The schematics of Al/SA/Al, Al/SAC/Al, and Cu/SA/Al at initial state and 1000 h aging described the interfacial morphology evolution of the joints. A binary phase diagram was proposed using CALPHAD method to explain the IMC formation sequence of Al/SAC/Al joints. The influence of Cu presence and concentration on interfacial reactions and microstructure of Al direct soldering was discussed.